Effectiveness of oral health promotion in children and adolescents through behaviour change interventions: A scoping review. - Fathima Peerbhay; Robert Mash; Saadika Khan (PLoS ONE)
Objective To explore the interventions for change in oral health behaviour that are effective in improving oral health behaviours in 8 to 18-year-old children during oral health promotion. Methods The Joanna Briggs Institute framework of evidence synthesis for conducting a scoping review was implemented for the methodology. Included studies related to the objective, measured clinical or non-clinical outcomes, were in English, 2011-2023, and were experimental, observational or reviews. PUBMED, Science-Direct, Scopus and Sabinet were systematically searched with predetermined search strings. Studies were selected by appraisal of the title, abstract and full text. Data were extracted using a standardised template and the key questions were addressed via a qualitative analysis. Results Searches yielded 407 articles from electronic databases. Of these, 290 articles were excluded, and 47 full-text studies were assessed for eligibility, with 23 studies and two systematic reviews finalised for inclusion. In addition, a PEARL search was conducted from the reference lists of other studies. Most studies (91.3%) focused on educating children directly; 8.7% indirectly influenced parents, guardians, and teachers. Interventions focused largely on traditional oral health education presented in diverse forms and via different platforms. Studies differentiated clinical outcomes (indices) from non-clinical outcomes (knowledge, behaviour). All included RCTs were of different quality regarding selection, performance and detection bias. But all studies indicated a low risk of bias in attrition and Reporting bias. Seventeen of the 25 studies (68%) were not based on any behaviour change theory. Conclusions Oral health interventions based on motivational interviewing and the social cognitive theory have been shown to be to be effective. Interventions could also include practical tooth brushing activities, gamification, audio-visual components, as well as reinforcement and repetition in the longer term. Future oral health promotion in children should be designed to include these elements. There is a need for higher quality studies in this field, with future research being urged to provide detailed intervention descriptions and incorporate longer follow-up periods.